Efficacy of Statins in Dyslipidemia: A Non interventional comparative study in a tertiary care hospital, Ajman, UAE - John, LJ; Esheiba, EM; Fathi, MAM; Agarwal, AK; Sreedharan, J; Muttappallymyalil, J; Shantakumari, N (Nepal Journal of Epidemiology, 2014)
Background The reduction of serum total cholesterol and LDL-cholesterol levels varies with different statins. The objective of the present study was to compare the efficacy of Simvastatin, Atorvastatin and Rosuvastatin in the treatment of newly diagnosed dyslipidemia. Material and Methods: A prospective, non-interventional 12-week study was conducted after approval from the Ethics Committee. A total of 70 patients with newly diagnosed dyslipidemia receiving 20mg of Simvastatin, Atorvastatin or Rosuvastatin were included. The primary efficacy measure was reduction of lipid levels from the initial baseline values at the end of 12 weeks with the respective Statins. Data was analyzed using descriptive statistics, Paired -t test, and analysis of variance (ANOVA). Results: Of total 70 patients, 14 patients received Simvastatin; 40 patients received Atorvastatin and 16 patients received Rosuvastatin. Demographic and baseline clinical characteristics were similar between the three groups. Significant reduction in lipid levels (total cholesterol, and LDL) was seen within the three treatment groups (p<0.01). However, statistically significant difference in the reduction lipid levels was not observed between the three groups. Conclusion: We found no significant difference in the reduction of lipid levels between Simvastatin, Atorvastatin or Rosuvastatin patients with newly diagnosed dyslipidemia. DOI: http://dx.doi.org/10.3126/nje.v4i5.12023 Nepal Journal of Epidemiology 2014; 4(5):428-32